New targets of nascent lymphatic vessels in ocular diseases - Wu, Xuhui; Ma, Yunkun; Zhang, Zhaochen; Hou, Tingting; He, Yuxi (Frontiers in Physiology, 2024)
Recent advancements in the field of endothelial markers of lymphatic vessels and lymphangiogenic factors have shed light on the association between several ocular diseases and ocular nascent lymphatic vessels. The immune privilege of corneal tissue typically limits the formation of lymphatic vessels in a healthy eye. However, vessels in the eyes can potentially undergo lymphangiogenesis and be conditionally activated. It is evident that nascent lymphatic vessels in the eyes contribute to various ocular pathologies. Conversely, lymphatic vessels are present in the corneal limbus, ciliary body, lacrimal glands, optic nerve sheaths, and extraocular muscles, while a lymphatic vasculature-like system exists in the choroid, that can potentially cause several ocular pathologies. Moreover, numerous studies indicate that many ocular diseases can influence or activate nascent lymphatic vessels, ultimately affecting patient prognosis. By understanding the mechanisms underlying the onset, development, and regression of ocular nascent lymphatic vessels, as well as exploring related research on ocular diseases, this article aims to offer novel perspectives for the treatment of such conditions.